Design and Integration of Information Systems for the Halal Inspection Institute (LPH) UIN Syarif Hidayatullah Jakarta with SiHalal Ministry of Religion of the Republic of Indonesia - Hidayah, Nur Aeni; Amri, Faaza Bil; Mutholib, Abdul (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2024)
In the context of the globalization of the halal industry, the Halal Inspection Institute (LPH) UIN Syarif Hidayatullah Jakarta faces challenges in improving halal certification services. This research develops a web-based information system with the integration of the Indonesian Ministry of Religion's SiHalal using the REST API and Prototype model. The main goal is to increase LPH credibility, integrate the LPH system with SiHalal, and improve LPH operational management performance. The system development method used is the Prototype Model, involving data collection through observation, interviews, and literature study to understand user needs. The first stage focuses on communication to understand needs, followed by rapid planning and prototype design. System implementation using JavaScript, NodeJs, and ReactJs. After a series of tests, the system resulted in effective integration with SiHalal and more efficient operational management. The research results include three prototypes. The first prototype focused on building an LPH profile website to increase credibility and access to information. The second prototype successfully integrated the LPH system with SiHalal, ensuring the efficiency and validity of audit reports. The third prototype adds report management, income/expenditure recording, and information updates, increasing LPH's operational efficiency.